Strategi Gereja Katolik Dalam Mempertahankan Eksistensi Umat Katolik Di Kabupaten Bangkalan Madura - Irda Hilyatuz Zakiyah; Agustinus Raja Dasion (Journal of Social, Culture, and Language, 2023)
Bangkalan Regency is predominantly Muslim. Although it is famous for its Islamic bigotry, people of other religions such as Catholics also coexist well there and have no difficulty in adapting to Muslims. The existence of a majority and minority can often lead to conflict, which can often threaten the existence of the minority. Therefore, the role of the Church as a forum for Catholics needs to be highlighted in the community. As a religious formation institution, it distributes its role to every young Catholic family to create family harmony and guide their offspring for the future of the Church and Catholics. This research uses a type of qualitative research with observation, interview, and documentation techniques.then analyzed theoretically with Pierre Bourdieu's theory of capital and arenas that can be used by individuals to control their fate and the fate of others.The location of this research was carried out in 3 Catholic Churches in Bangkalan Regency, including: St. Maria Fatima Catholic Church, St. Maria Immaculata Stasi Telang Catholic Church, and GPdI Tanjung Bumi and SDK Maria Fatima Bangkalan. That Catholics can participate in the social activities of the local community shows that the existence of Catholics in Bangkalan today is arguably quite good. Catholics in Bangkalan maintain their existence and religious sovereignty by joining local associations, participating in village activities, providing guidance to children, and providing religious education through schools. If analyzed with Bourdieu's theory, Catholics can utilize their symbolic, economic, linguistic, and social capital, they can expand their power and influence in Bangkalan. Keywords: Existence, Catholic Church, Catholics